Pengaruh Penambahan Abu Serbuk Kayu Dan Serbuk Batu Bata Berdasarkan Uji Konsolidasi Dan Waktu Penurunan Tanah Lempung - Ranggaski Yoan Vianus; Mohammad Ikhwan Yani; Fatma Sarie (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
The waste from the wood and brick industry in Central Kalimantan is largely unused. The research objective aims to analyze the physical and mechanical properties of clay soil in the Tumbang Rungan area of ​​Palangka Raya City, Central Kalimantan and the effect of adding sawdust ash and brick powder based on the consolidation test and the time of subsidence of the clay soil using the Terzaghi one-dimensional consolidation method with the addition of a mixture of 2 variations 2,5%, 5% and 7,5%. Tests conducted are to obtain the consolidation reduction value (Sc) and the consolidation coefficient value (Cv). The results of the study using a mixture of sawdust ash and brick powder obtained changes in the Sc and Cv values ​​of the original soil. The original soil has a value of Sc (e) = 0.291 cm and Cv (t50) = 0.01913205 cm²/s, Cv (t90) = 0.031062161 cm²/s and the addition of a mixture of 5% variation of material has decreased the value of Sc (e) = 0.203 cm and Cv (t50) = 0.00722173 cm²/s, Cv (t90) = 0.011679143 cm²/s. The effective mixture variation for adding mixed material to clay is a variation of 5%.